Dari Mimpi ke Realita: Membangun Robot Bersama Siswa MAN 1 Madiun - Sukoco Didik; Imam Sutrisno; Projek Priyonggo; Iskandar (CV. Creative Tugu Pena, 2025)
Project-Based Learning (PBL) has proven to be an effective pedagogical approach for enhancing students' competencies in technology and engineering. This study aims to explore the processes and outcomes of a robotics development project conducted by students of MAN 1 Madiun through extracurricular robotics activities. Employing a qualitative case study method, data were collected via observations, interviews, and document analysis. The results indicate that active student participation in the robotics project significantly improved their critical thinking, problem-solving, creativity, and teamwork skills. The presence of teacher guidance and adequate laboratory facilities was found to be instrumental in supporting the program’s success. This research offers several key contributions to technology education, particularly within Islamic secondary school settings. First, it demonstrates the adaptability of PBL in contexts where robotics is not part of the standard curriculum. Second, it highlights the development of both technical skills—such as electronic assembly, Arduino programming, and mechanical design—and soft skills essential for 21st-century learning. Third, the study presents empirical evidence that hands-on robotics projects can lead to increased student motivation and deeper understanding of STEM concepts. Additionally, the research proposes a practical and replicable model for implementing robotics-based programs in schools, identifying key success factors such as mentorship, infrastructure, and institutional support. Lastly, by engaging students in real-world project cycles—designing, building, testing, and refining—the initiative contributes to bridging the gap between school curricula and the collaborative, problem-solving demands of Industry 4.0